Exploring Genetic Factors Associated with Moniezia spp. Tapeworm Resistance in Central Anatolian Merino Sheep via GWAS Approach - Yunus Arzik; Mehmet Kizilaslan; Sedat Behrem; Lindsay M. W. Piel; Stephen N. White; Mehmet Ulaş Çınar (Animals)
Gastrointestinal parasite (GIP) infections pose significant challenges in pasture-based sheep farming, leading to economic losses and welfare concerns. This study aimed to uncover the genetic basis of resistance to Moniezia spp. infections in Central Anatolian Merino (CAM) sheep. Genome-Wide Association Analysis (GWAS) was conducted between Moniezia spp. egg burden and genomic data from 226 CAM lambs. Thirteen significant Single-Nucleotide Polymorphisms (SNPs) were identified, with five surpassing the genome-wide threshold and eight exceeding the chromosome-wide threshold. Functional annotation revealed associations with genes involved in immune function, notably CD79A and MAP3K7. CD79A, integral to B-cell activation and antibody production, plays a key role in the immune response against parasitic infections. Its interaction with helminth-derived proteins modulates B-cell function, highlighting its potential as a therapeutic target. MAP3K7, a central regulator of immune signaling pathways, modulates host responses to helminth infections by influencing NF-κB activity. Additionally, it regulates macrophage function in bacterial infections, showcasing its versatility in mediating immune responses against diverse pathogens. From a practical perspective, the findings of the current research underscore the potential of integrating genomic information into breeding programs to bolster disease resilience in livestock populations for sustainable production purposes. However, further research is needed to elucidate the functional significance of identified SNPs and associated genes. This study underscores the potential of genomic approaches in combating parasitic diseases and promoting sustainable agriculture in sheep production systems.